Functional and Structural Architectures of Allocentric and Egocentric Spatial Coding in Aging: A Combined DTI and fMRI Study - Derbie, Abiot Y.; Chau, Bolton K. H.; Chan, Chetwyn C. H. (Frontiers in neurology, 2022)
Aging disrupts the optimal balance between neural nodes underlying orienting and attention control functions. Previous studies have suggested that age-related changes in cognitive process are associated to the changes in the myelinated fiber bundles, which affected the speed and actions of the signal propagation across different neural networks. However, whether the age-related difference in allocentric and egocentric spatial coding is accounted by the difference in white-matter integrity is unclear. In this study, using diffusion tensor imaging (DTI) and functional magnetic resonance imaging (fMRI), we sought to elucidate whether age-related differences in white matter integrity accounts for the difference in nodes to the distributed spatial coding-relevant brain networks. Older ( = 24) and younger ( = 27) participants completed the structural DTI and fMRI scans during which they engaged in a cue-to-target task to elicit allocentric or egocentric processes. Efficient modulation of both allocentric and egocentric spatial coding in fronto-parietal attention network (FPAN) requires structure-function interaction. Allocentric task-modulated connectivity of the fronto-parietal network (FPN) and dorsal attention network (DAN) with the temporal lobe was influenced by the aging differences of the white-matter tracts of the posterior and superior corona radiata (PCR and SCR), respectively. On the other hand, aging difference of the superior longitudinal fasciculus mainly influenced the egocentric-task-modulated connections of the DAN and FPN with frontal regions and posterior cingulate cortex. This study suggested that functional connections of the FPAN with near and far task-relevant nodes vary significantly with age and conditions.